The Influence of Two Stay Two Stray Learning Model on Motivation and Mathematics Learning Outcomes of Class IV Students, Tellu Siattinge District, Bone Regency - Bahrum; Baharullah; Husniati (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2022)
This research aims to describe the improvement of student learning outcomes and motivation using the Two Stay Two Stray type of cooperative learning model in learning mathematics. The method used is the Quasy Experimental Design research method. This study aims to find the effect caused by the treatment or treatment in the form of the use of cooperative learning models in learning mathematics on motivation and learning outcomes. This study's data analysis technique used descriptive statistical and inferential statistical analysis. And statistical calculations, namely normality test and homogeneity test. After that, the hypothesis was tested using the t-test. The results showed that 1) the results of the descriptive analysis were found in the experimental class using the Two Stay Two Stray type of cooperative learning model with a total score of 1,828 with an average of 79 of 23 students; 2) students' learning motivation uses the Two Stay Two Stray type of cooperative learning model in learning mathematics with a total score of 2008 with an average of 87 of 23 students; 3) the value of student learning outcomes in the control class is 64 and in the experimental class using the Two Stay Two Stray type of cooperative learning model is 79. So the difference in these values ​​can be concluded that learning using the Two Stay Two Stray type of cooperative learning model is much better used in the teaching and learning process